Development of Media Technologies as “New Media” from the Perspective of a Critique of the Political Economy of the Media - Manfred Knoche (tripleC: Communication, Capitalism & Critique. Open Access Journal for a Global Sustainable Information Society, 2024)
This paper analyses the emergence and development of new media technologies based on the approach of the Critique of the Political Economy of the Media. First, a critical overview of approaches to the genesis and diffusion of technologies is given. Second, the connection between media technologies and capital accumulation is discussed. Third, the role of media technologies in capitalism as a means of investment, production, distribution, and consumption is analysed. Fourth, the connection between innovation, commodity aesthetics, and planned obsolescence is discussed. Fifth, the antagonistic character of the media system's convergence, universalisation and diversification is shown. The article shows that technological development is not autonomous but depends on and is shaped by the development of capitalist society. In capitalism, factors such as capital accumulation strategies, crises, competition, advertising and marketing, market research, the state's economic, technology and media policies, and science and engineering influence the emergence and development of new media technologies.Acknowledgement: This article was first published as book chapter: Manfred Knoche. 2005. Entwicklung von Medientechnologien als ,,Neue Medien“ aus der Perspektive einer Kritik der~ politischen Ökonomie der Medien. In Alte Medien – neue Medien: Theorieperspektiven, Medienprofile, Einsatzfelder. Festschrift für Jan Tonnemacher, edited by Klaus Arnold and Christoph Neuberger, 40-62.~ Wiesbaden: VS Verlag für Sozialwissenschaften.~ Translated and published with permission by SNCSC. ~
Keywords: 330; new media; Kritik der politischen Ökonomie der Medien; Critique of the Political Economy of the Media